حقوق أطفال التوحد وأسرهم في إطار الشريعة الإسلامية - Thawab, Al-Quran; Nashaat, Baioumy; Ab. Aziz, Sulaiman (2018)
Autistic children suffer from many problems and challenges that affect their role in serving the society. The autistic child needs specialized care, great attention and careful monitoring by his family. This is a double burden on the child and the family, which making them unable to integrate and engage in the society and here lies the problem of the research. In this paper, the researcher wishes to mention the role of Islam in taking into consideration the conditions of people with developmental disabilities, in addition to knowing their rights and the rights of their families, using the descriptive analytical approach and the deductive approach. The results showed the greatness of Islam in dealing with this category and other various disabilities by giving them the most basic rights to provide a decent life for everyone regardless of shape, color, sex or class, in addition to satisfy all the needs in accordance with Islamic rules.